COVID-19 in hospitalized HIV-positive and HIV-negative patients: A matched study - Díez, Cristina; Del Romero-Raposo, Jorge; Mican, Rafael; López, Juan C.; Blanco, José R.; Calzado, Sonia; Samperiz, Gloria; Portilla, Joaquín; García-Fraile, Lucio J.; Gutiérrez, Félix; Gómez-Sirvent, Juan L.; Suárez-García, Inés; et al. (Wiley, 2021)
Objectives: We compared the characteristics and clinical outcomes of hospitalized individuals with COVID-19 with [people with HIV (PWH)] and without (non-PWH) HIV co-infection in Spain during the first wave of the pandemic. Methods: This was a retrospective matched cohort study. People with HIV were identi fied by reviewing clinical records and laboratory registries of 10 922 patients in active follow-up within the Spanish HIV Research Network (CoRIS) up to 30 June 2020. Each hospitalized PWH was matched with five non-PWH of the same age and sex randomly selected from COVID-19@Spain, a multicentre cohort of 4035 patients hospitalized with confirmed COVID-19. The main outcome was all-cause in-hospital mortality. Results: Forty-five PWH with PCR-confirmed COVID-19 were identified in CoRIS, 21 of whom were hospitalized. A total of 105 age/sex-matched controls were selected from the COVID-19@Spain cohort. The median age in both groups was 53 (Q1¿Q3, 46¿56) years, and 90.5% were men. In PWH, 19.1% were injecting drug users, 95.2% were on antiretroviral therapy, 94.4% had HIV-RNA < 50 copies/mL, and the median (Q1¿Q3) CD4 count was 595 (349¿798) cells/¿L. No statistically significant differ ences were found between PWH and non-PWH in number of comorbidities, pre senting signs and symptoms, laboratory parameters, radiology findings and severity scores on admission. Corticosteroids were administered to 33.3% and 27.4% of PWH and non-PWH, respectively (P = 0.580). Deaths during admission were documented in two (9.5%) PWH and 12 (11.4%) non-PWH (P = 0.800). Conclusions: Our findings suggest that well-controlled HIV infection does not modify the clinical presentation or worsen clinical outcomes of COVID-19 hospitalization.